The relationship between specialized pro-resolving lipid mediators, morbid obesity and weight loss after bariatric surgery - Schulte, Fabian; Asbeutah, Abdul Aziz; Benotti, Peter N.; Wood, G. Craig; Still, Christopher; Bistrian, Bruce R.; Hardt, Markus; Welty, Francine K. (Scientific reports, 2020)
Obesity and diabetes are associated with chronic inflammation. Specialized pro-resolving lipid mediators (SPMs)—resolvins (Rv), protectins (PD) and maresins (MaR)—actively resolve inflammation. Bariatric surgery achieves remission of diabetes, but mechanisms are unclear. We measured SPMs and proinflammatory eicosanoid levels using liquid chromatography-tandem mass spectrometry in 29 morbidly obese subjects (13 with diabetes) and 15 nondiabetic, mildly obese subjects. Compared to the mildly obese, the morbidly obese had higher levels of SPMs—RvD3, RvD4 and PD1—and white blood cells (WBC) and platelets. Post-surgery, SPM and platelet levels decreased in morbidly obese nondiabetic subjects but not in diabetic subjects, suggesting continued inflammation. Despite similar weight reductions 1 year after surgery (44.6% vs. 46.6%), 8 diabetes remitters had significant reductions in WBC and platelet counts whereas five non-remitters did not. Remitters had a 58.2% decrease ( p = 0.03) in 14-HDHA, a maresin pathway marker; non-remitters had an 875.7% increase in 14-HDHA but a 36.9% decrease in MaR1 to a median of 0. In conclusion, higher levels of RvD3, PD1 and their pathway marker, 17-HDHA, are markers of leukocyte activation and inflammation in morbid obesity and diabetes and diminish with weight loss in nondiabetic but not diabetic subjects, possibly representing sustained inflammation in the latter. Lack of diabetes remission after surgically-induced weight loss may be associated with reduced ability to produce MaR1 and sustained inflammation.